2000
DOI: 10.1111/1468-0351.00055
|View full text |Cite
|
Sign up to set email alerts
|

Intervention, Corruption and Capture: The Nexus between Enterprises and the State

Abstract: We study the nexus between enterprises and the state in transition countries, using new enterprise survey data. We examine the quality of governance, state intervention in enterprise decision-making, state benefits to firms, and corruption payments. The quality of governance varies both across countries and across different dimensions of governance within countries. Economic reform improves governance in countries with a low degree of 'state capture' by vested interests, but not in high-capture countries. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 11 publications
(10 reference statements)
2
56
1
3
Order By: Relevance
“…They also strived to establish market-oriented institutions and a legal system that would improve the role of the state in providing infrastructure vital to the newly emerging market economy (state governance). Despite the considerable achievements during the first decade of transition, Hellman and Schankerman (2000) showed that good state governance was not established across many transformation economies by 1999.…”
Section: Introductionmentioning
confidence: 99%
“…They also strived to establish market-oriented institutions and a legal system that would improve the role of the state in providing infrastructure vital to the newly emerging market economy (state governance). Despite the considerable achievements during the first decade of transition, Hellman and Schankerman (2000) showed that good state governance was not established across many transformation economies by 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Ill-designed, rapid transfer of rent-generating assets could create powerful private players interested in protecting their interests at the cost of potential competition. Resulting structures of political capitalism could be at least as dangerous in their political influence on the reform process as a large residual state sector (Hellman and Schankerman, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Most recent evidence indicates that the rapid privatisation methods, in particular the mass privatisation programmes, were associated with good macro performance, contrary to earlier criticism (Bennett et al, 2007) 7 . The underlying reason may be that mass privatisation severed the links between the companies and the state early on, which was a critical factor cutting flows of state funds to failing firms and triggering restructuring (Hellman and Schankerman, 2000;Estrin, 2002). In addition, mass privatisation initiated the subsequent evolution in ownership structures.…”
Section: Mass (Voucher) Privatisationmentioning
confidence: 99%
“…Hellman and Schankerman (2000) showed that within a country, economic reforms improve governance in countries with interest groups that lack the ability or will to influence government policies.…”
Section: Appendix Amentioning
confidence: 99%